PENGARUH ICE BREAKING TERHADAP MOTIVASI BELAJAR SISWA KELAS III DI SDN 066656 MEDAN - Sembiring, Polintan Rehulina; Tarigan, Rupina Magdalena Br; Manik, Nova Betania (Jurnal Curere, 2024)
Ice breaking is a way to break monotonous situations, ice breaking can build a learning atmosphere full of enthusiasm and enthusiasm. The research aims to determine the effect of ice breaking on the learning motivation of class III students at SDN 066656 Medan. The type of research used is experimental. The research used Pre-Experiment in the form of The One Group Pretest-Posttest. The population in the study was class III students at SDN 066656 Medan consisting of 25 students consisting of 12 boys and 13 girls. Data collection techniques in research are observation, questionnaires and documentation. The data analysis technique in this research is descriptive analysis, prerequisite tests, namely normality test, homogeneity test and hypothesis test. The data normality test value is 0.211, which means the population is normally distributed, then the homogeneity test obtained a value of 0.219, which means the homogeneity test is fulfilled. Hypothesis testing obtained a value of 0.000, which means that there is an influence of ice breaking on the learning motivation of class III students at SDN 066656 Medan.